Participation or legitimisation? Assessment of quality of participation in farmer learning video production in central Uganda - Tamubula, I.B.; Sseguya, H.; Mirro, R.; Okry, F. (Informa UK Limited, 2020)
Purpose: This study assessed the quality of participation in farmer learning video (FLV) production by examining opportunities for actors’ participation and the extent of incorporation of their interests.